2014
DOI: 10.1021/ar400293h
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions and Intrinsically Disordered Proteins and Peptides: From Cu/Zn Amyloid-β to General Principles

Abstract: The interaction of d-block metal ions (Cu, Zn, Fe, etc.) with intrinsically disordered proteins (IDPs) has gained interest, partly due to their proposed roles in several diseases, mainly neurodegenerative. A prominent member of IDPs is the peptide amyloid-β (Aβ) that aggregates into metal-enriched amyloid plaques, a hallmark of Alzheimer's disease, in which Cu and Zn are bound to Aβ. IDPs are a class of proteins and peptides that lack a unique 3D structure when the protein is isolated. This disordered structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
240
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 232 publications
(255 citation statements)
references
References 47 publications
9
240
1
5
Order By: Relevance
“…Metals are known to play a key role in this oxidative stress and also to be associated with peptide aggregation, at the core of the pathology (Faller et al, 2013;Viles, 2012). More specifically, Cu II has been found to form a complex with the amyloid peptide for which aggregation is one of the major hallmarks of AD (Eury et al, 2011;Faller et al, 2014). This has triggered significant ongoing interest in the development of chelators able to interact with metals in the context of AD (Santos et al, 2016;Conte-Daban et al, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Metals are known to play a key role in this oxidative stress and also to be associated with peptide aggregation, at the core of the pathology (Faller et al, 2013;Viles, 2012). More specifically, Cu II has been found to form a complex with the amyloid peptide for which aggregation is one of the major hallmarks of AD (Eury et al, 2011;Faller et al, 2014). This has triggered significant ongoing interest in the development of chelators able to interact with metals in the context of AD (Santos et al, 2016;Conte-Daban et al, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…24,27,28 On the other hand, it has been observed that substoichiometric amounts of Cu(II) can nucleate fibril formation and that the Cu(II)-generated fibers are capable of seeding fiber formation of metal-free Aβ (as indicated by a reduction in the lag time); See in line with the expected behaviour of intrinsically disordered proteins. 6 Though, surface-plasmon resonance (SPR) biosensing experiments have shown that these Cu(II)-induced aggregates are unstable. 25 Both the nucleation and elongation rates are accelerated by Cu(II) ions for Aβ 40 and Aβ 42 , independently of the pH, the enhancement being significantly higher for Aβ 42 for which the total fiber content is superior.…”
Section: Copper-induced Aβ Aggregationmentioning
confidence: 99%
“…The content of defined structure depends strongly on external conditions and interactions with other biomolecules and metal ions. 6 An imbalance of metal-ion homeostasis in the brain is thought to play an important role in the pathogenesis of AD. The concentrations of Cu, Zn and Fe in the brain are tightly regulated in the central nervous system (CNS) at the level of the blood-brain barrier (BBB).…”
mentioning
confidence: 99%
See 2 more Smart Citations